2024
DOI: 10.7554/elife.89093
|View full text |Cite
|
Sign up to set email alerts
|

Reward contingency gates selective cholinergic suppression of amygdala neurons

Abstract: Basal forebrain cholinergic neurons modulate how organisms process and respond to environmental stimuli through impacts on arousal, attention, and memory. It is unknown, however, whether basal forebrain cholinergic neurons are directly involved in conditioned behavior, independent of secondary roles in the processing of external stimuli. Using fluorescent imaging, we found that cholinergic neurons are active during behavioral responding for a reward – even in prior to reward delivery and in the absence of disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 106 publications
0
0
0
Order By: Relevance
“…Consistent with prior observations 15,25 , we found that activation of the SI ChAT →BLA pathway did not induce any place preference (Figures S5G and S5H), or affect the movement (Figures S5I and S5J). In addition, activation of this pathway failed to support self-stimulation (Figures S5K-S5N).…”
Section: Activation Of Si Cholinergic Neurons and Sisupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with prior observations 15,25 , we found that activation of the SI ChAT →BLA pathway did not induce any place preference (Figures S5G and S5H), or affect the movement (Figures S5I and S5J). In addition, activation of this pathway failed to support self-stimulation (Figures S5K-S5N).…”
Section: Activation Of Si Cholinergic Neurons and Sisupporting
confidence: 92%
“…Previous studies have shown that acetylcholine (ACh) is a key neuromodulator critical for conscious awareness, salience, and attentional control, and is essential for associative learning and memory [7][8][9][10][11][12][13][14][15]15,16,[16][17][18][19] . Cholinergic deficiencies represent a prominent feature of attention-related impairments observed in Alzheimer's disease and Parkinson's dementia 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation